2016
DOI: 10.18632/aging.101026
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrogen sulfide in aging and age-related pathologies

Abstract: When humans grow older, they experience inevitable and progressive loss of physiological function, ultimately leading to death. Research on aging largely focuses on the identification of mechanisms involved in the aging process. Several proposed aging theories were recently combined as the ‘hallmarks of aging’. These hallmarks describe (patho-)physiological processes that together, when disrupted, determine the aging phenotype. Sustaining evidence shows a potential role for hydrogen sulfide (H2S) in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 293 publications
3
67
0
Order By: Relevance
“…Hydrogen sulfide (H 2 S), a metabolic product of methionine, is synthesized from L-cysteine primarily by three key enzymes: cystathionine-c-lyase (CGL), cystathionine-b-synthetase (CBS) and 3-mercaptypyruvate sulfurtransferase (MPST). Identified as the third gasotransmitter, along with nitric oxide and carbon monoxide, H 2 S modulates a variety of physiological functions including anti-oxidative stress, anti-senescence/aging, and anti-apoptotic effects ( 104 106 ). H 2 S has been proposed as serving as a potent antioxidant through reactive oxygen species/reactive nitrogen species scavenging, or through post-translational modification of proteins by addition of a thiol (-SH) group onto reactive cysteine residues ( 107 ).…”
Section: Therapeutic Strategies Targeting Inflammation Oxidative Strmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S), a metabolic product of methionine, is synthesized from L-cysteine primarily by three key enzymes: cystathionine-c-lyase (CGL), cystathionine-b-synthetase (CBS) and 3-mercaptypyruvate sulfurtransferase (MPST). Identified as the third gasotransmitter, along with nitric oxide and carbon monoxide, H 2 S modulates a variety of physiological functions including anti-oxidative stress, anti-senescence/aging, and anti-apoptotic effects ( 104 106 ). H 2 S has been proposed as serving as a potent antioxidant through reactive oxygen species/reactive nitrogen species scavenging, or through post-translational modification of proteins by addition of a thiol (-SH) group onto reactive cysteine residues ( 107 ).…”
Section: Therapeutic Strategies Targeting Inflammation Oxidative Strmentioning
confidence: 99%
“…Exogenously provided H2S, either in gas form or via donor molecules, increases lifespan in model organisms (Miller and Roth, 2007), prevents multi-tissue ischemic-reperfusion injury (Elrod et al, 2007;Hine et al, 2015), improves cardiovascular health Yang et al, 2008), and is recognized as a potential therapeutic agent against aging-associated diseases (Zhang et al, 2013). Conversely, deficiencies in endogenous H2S levels or production correlate with and/or are causative of hypertension (Yang et al, 2008), colitis (Flannigan et al, 2014), neurodegeneration (Sbodio et al, 2016), and glioma growth (Takano et al, 2014) while H2S levels in humans are reported to decline during aging, particularly those suffering from COPD (Chen et al, 2005;Perridon et al, 2016). Thus, the field of H2S in biology, physiology, and medicine has blossomed (Wallace and Wang, 2015;Wang, 2012), with endogenous H2S serving as a therapeutic target and the third functional gasotransmitter alongside carbon monoxide and nitric oxide (Paul and Snyder, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the train of the above observations, we wish to underscore that H 2 S is both an anti-aging mechanism and a hallmark of aging (Perridon et al 2016) and the progressive decline of its availability may explain the age pattern of Covid 19. Indeed, H 2 S is to our knowledge the best characterized inducer of Treg lymphocyte differentiation (Yang et al 2015) and any decline of its release associates with derangement of innate immunity.…”
Section: Age and Sex Ratio Of Covid 19mentioning
confidence: 89%